Optimal satellite shielding and orbital debris - Bongers-Chicano, Aneli María; Molinari, Benedetto; Torres-Chacón, José Luis (Springer, 2026)
Orbital debris, or space junk, is a major environmental externality that poses serious risks to human activity in outer space. The rapid increase in satellites and spacecraft from commercial, military, and scientific missions has intensified space pollution, leaving millions of debris fragments orbiting Earth at high velocities. This proliferation raises the likelihood of collisions and the destruction of operational spacecraft. This paper examines how spacecraft shielding affects both collision-related damage and debris generation. Shielding lowers the probability of satellite breakup during collisions, helping limit the creation of additional debris. It illustrates how spacefaring firms can mitigate the environmental costs of space activity through individual actions, even within a decentralized, profit-driven framework. Our analysis shows that when satellite operators invest in reducing collision risks and potential destruction, their behavior partially internalizes the externality, improving orbital sustainability. However, the optimal level of shielding in a decentralized economy remains below that achieved under a centralized framework, demonstrating that market mechanisms only partially address the negative externality.
Keywords: Basura espacial; Impacto; Orbital debris; Satellites; Risk of collision; Shielding